Capturing Human Movements in Real Time in Collaborative Robots Workspace within Industry 5.0 (Journal of Universal Science Research, 2024)
The article examines the application of technologies for capturing human movements in real time in collaborative robots workspace ​​ in the context of Industry 5.0. Mathematical apparatus and software for analyzing movements with high accuracy has been developed, which allows to increase the safety and efficiency of human-robot interaction. The conducted experiments showed the influence of lighting conditions and movements speed on the accuracy of movements capture and visualization, which is critically important for the optimal operation of collaborative robots in production environments.